Marketing research of motivation factors of a multicultural team - Yu. P. Soboleva; I. P. Timofeeva; A. V. Romanova (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. In connection with the expansion of relations with post-Soviet states and the turn of domestic companies to external personnel marketing, multicultural labor teams are being formed. Work with multinational labor groups requires a special approach due to the large socio-cultural differences of the nations that make up such teams. Projects realized beyond national borders create specific problems for managers. In this aspect, cross-cultural marketing is an important tool for building long-term cooperation in working with multicultural teams.Goal. The study aims to identify the motives of behavior of labor migrants from the Republic of Uzbekistan working in the Russian Federation.Materials and methods. The paper presents the results of a marketing research on the identification of labor motives in order to further develop practical recommendations for the effective management of multicultural teams. A questionnaire survey was conducted to identify the system of values underlying the labor behavior of migrants.Results and discussion. The structure of generations of labor migrants from the Republic of Uzbekistan was formed. The analysis of labor motives in the context of age generations – “Boomers”, “X”, “Y” and “Z” – and correlation of this classification with the system of personnel motivation was given.Conclusion. The provisions and conclusions of this paper can be used to develop incentive measures in the field of multicultural team management.